The Natural Compound Neobractatin Induces Cell Cycle Arrest by Regulating E2F1 and Gadd45α - Zheng, Zhaoqing; Wu, Man; Zhang, Juan; Fu, Wenwei; Xu, Naihan; Lao, Yuanzhi; Lin, Lan; Xu, Hongxi (Frontiers in Oncology, 2019)
The complexity and multi-target feature of natural compounds have made it difficult to elucidate their mechanism of action (MoA), which hindered the development of lead anticancer compounds to some extent. In this study, we applied RNA-Seq and GSEA transcriptome analysis to rapidly and efficiently evaluate the anticancer mechanisms of neobractatin (NBT), a caged prenylxanthone isolated from the Chinese herb Garcinia bracteata. We found that NBT exerted anti-proliferative effect on various cancer cells and caused both G1/S and G2/M arrest in synchronized cancer cells through its effects on the expression of E2F1 and GADD45α. The in vivo animal study further suggested that NBT could reduce tumor burden in HeLa xenograft model with no apparent toxicity. By demonstrating the biological effect of NBT, we provided evidences for further investigations of this novel natural compound with anticancer potential.